Desarrollo de un plan de negocios de turismo para el Lodge Caobas de Saa En el sitio Tillales, cantón El Guabo. - Polit Bermeo, Maytee Solange (Machala : Universidad Técnica de Machala, 2023)
The comprehensive research on Lodge Caobas by SAA reveals crucial insights for the ever-evolving hotel industry. Emphasizing customers' unequivocal preference for private transportation and the decisive influence of social media and email on their choices, there is a pressing need to customize experiences to meet market expectations. Furthermore, a potentially lucrative market segment is identified: friend groups with a budget exceeding forty US dollars, comprising more than five members. This discovery presents a strategic opportunity to tailor the lodge's offerings and services to meet the specific demands of this segment. The analysis also highlights critical areas for improvement, spanning from infrastructure to sustainability and environmental preservation. Emphasis is placed on the necessity to implement personalized tourism promotion strategies and stay abreast of technological trends to maintain the Lodge's competitiveness. Additionally, sustainability and responsibility are established as fundamental pillars, supported by the implementation of a comprehensive sustainable development plan based on a specific model. This approach ensures that Lodge Caobas by SAA's growth aligns harmoniously with the environment and the community, underscoring the lodge's commitment to environmental preservation and the well-being of the local community. This establishes it as an innovative and responsible leader in the hotel industry.
La investigación exhaustiva sobre el Lodge Caobas de SAA revela datos cruciales para la industria hotelera en constante cambio. Destacando la preferencia inequívoca de los clientes por el transporte privado y la influencia decisiva de las redes sociales y el correo electrónico en sus elecciones, se subraya la necesidad apremiante de personalizar las experiencias para satisfacer las expectativas del mercado. Además, se identifica un segmento de mercado potencialmente lucrativo: grupos de amigos con un presupuesto superior a los cuarenta dólares estadounidenses, compuestos por más de cinco miembros. Este hallazgo proporciona una oportunidad estratégica para adaptar las ofertas y servicios del lodge y satisfacer las demandas específicas de este segmento. El análisis también resalta áreas críticas para la mejora, desde infraestructura hasta sostenibilidad y preservación del medio ambiente. Se enfatiza la necesidad de implementar estrategias de promoción turística personalizadas y de estar al tanto de las tendencias tecnológicas para mantener la competitividad del Lodge. Además, se establece la sostenibilidad y la responsabilidad como pilares fundamentales, apoyados por la implementación de un plan de desarrollo sostenible integral basado en un modelo específico. Este enfoque garantiza que el crecimiento del Lodge Caobas de SAA esté en armonía con el entorno y la comunidad, resaltando el compromiso del lodge con la preservación ambiental y el bienestar de la comunidad local, estableciéndolo como líder innovador y responsable en la industria hotelera.
Keywords: DESARROLLO SOSTENIBLE; COMPETITIVIDAD HOTELERA; EXPERIENCIAS PERSONALIZADAS; COMUNIDAD